THE ROLE OF LOCAL WISDOM IN STRENGTHENING THE EFFEVTIVENESS OF THE ADIWIYATA PROGRAM IN DEVELOPING STUDENTS’ ENVIRONMENTAL CHARACTER: A SYSTEMATIC LITERATURE REVIEW - Annisa, Selfiana; Faizah, Siti; Pristiani, Riska (STKIP Citra Bakti, 2026)
This study addresses the limited contextualization of environmental education in schools, which often reduces the effectiveness of the Adiwiyata Program in developing students’ environmental character. Although widely implemented, the program’s success depends on how environmental values are meaningfully internalized. This study aims to examine the role of local wisdom in strengthening the effectiveness of the Adiwiyata Program in fostering students’ environmental character. This research employs a Systematic Literature Review (SLR) using the PRISMA framework. A total of 10 articles were selected from the Scopus database based on predefined inclusion and exclusion criteria, focusing on studies related to Adiwiyata, environmental character, and local wisdom in school contexts. The findings indicate that the Adiwiyata Program significantly improves students’ environmental awareness, attitudes, and behaviors through participatory activities, school culture, and environmentally oriented curricula. Furthermore, the integration of local wisdom such as mutual cooperation and culturally based environmental practices strengthens program effectiveness by making learning more contextual and meaningful. In conclusion, local wisdom plays a crucial role in enhancing the effectiveness of the Adiwiyata Program. Integrating cultural values into environmental education supports more holistic and sustainable development of students’ environmental character.